Kolotsk Dormition Monastery in Manuscript Materials of the Russian State Library and Other Sources - Tatiana E. Zinkevich (Два века русской классики)
The article reviews the manuscript and printed sources related to the Koloch Icon of the Mother of God and the Kolotsk Dormition Monastery. A considerable part of the study relies on manuscripts from the Russian State Library. The article pays particular attention to literary works, which reflect the history of the discovery of the wonderworking icon and the stages of the monastery’s development from the 15th century to the present. The editions of the Tale of Luke of Koloch are considered on the example of the copies from the Manuscript Department of the Russian State Library. The research shows the necessity of studying the sources from several points of view, such as literary analysis of the text and axiological research. Such an approach shows the strengthening of Christian motifs in the copies of the 18th century. The article reveals a new copy of the beginning of the 20th century with a brief description of the Kolotsk monastery and introduces it into scientific circulation. The considered letters and memoirs describe the participation of the Kolotsk monastery in the events significant for Russia, including the Patriotic War of 1812.